Developing TaskBased Reading Materials to Improve EFL Students Critical Thinking in the Extensive Reading Class - Hanan, Ahmad; Terasne, Terasne; Permana, Dira (Riwayat: Educational Journal of History and Humanities, 2024)
This study aims to develop task-based instructional materials (Task-Based Learning/TBL) designed to enhance the critical thinking skills of EFL students in the Extensive Reading course at Universitas Pendidikan Mandalika. The research employs the Research Development (RD) method using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. In the analysis stage, observations and interviews were conducted to assess students' needs. During the development stage, reading materials covering themes such as environmental issues, cultural diversity, and technology were created to promote analytical thinking. Specific tasks included evaluating arguments, comparing perspectives, and synthesizing information from multiple texts. These tasks required students to not only comprehend the material but also apply critical thinking by questioning assumptions and drawing reasoned conclusions. The instructional materials were tested for practicality and used in both experimental and control classes, involving 70 fourth-semester students. Results showed that the materials were highly suitable for classroom use with minor revisions. Post-test results indicated that students in the experimental class demonstrated a significant increase in critical thinking skills, with an average score of 83.3, compared to 71.73 in the control group. These findings suggest that task-based instructional materials are effective in promoting critical thinking and can serve as an innovative tool in Extensive Reading instruction. Future research could explore the long-term effects of task-based learning on critical thinking skills in diverse EFL contexts, as well as investigate the integration of digital tools to further enhance student engagement and learning outcomes.